2004
DOI: 10.1007/s11249-004-8086-9
|View full text |Cite
|
Sign up to set email alerts
|

Dry Sliding Wear Model of Nanometer Scale Multilayered TiN/CrN PVD Hard Coatings

Abstract: Dry sliding wear resistance of nanomultilayered TiN/CrN coatings has been evaluated using a ball-on-disk tribometer and compared with TiN and CrN monolayered references. The significant extend of lifetime of the nanostratified coatings is explained by a particular stress field generated in the whole thickness and a degradation model is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 35 publications
(34 reference statements)
0
16
0
Order By: Relevance
“…The  of coatings increased from 4.9 nm at V s =-30 V to 6.3 nm at V s =-60 V, and then decreased to 5.2 nm at V s =-100 V. The change of  is attributed to the improved density of layers and increased elements resputtering effects with increasing V s [34]. structure with a strong (111)-texture, which represents the well-epitaxial growth of CrN fcc phase on TiN (111) [16,34]. The narrow width of (111) peaks indicates a high degree of crystallinity [16].…”
Section: Chemical Composition and Structure Of Crn/tin Superlattice Cmentioning
confidence: 94%
See 2 more Smart Citations
“…The  of coatings increased from 4.9 nm at V s =-30 V to 6.3 nm at V s =-60 V, and then decreased to 5.2 nm at V s =-100 V. The change of  is attributed to the improved density of layers and increased elements resputtering effects with increasing V s [34]. structure with a strong (111)-texture, which represents the well-epitaxial growth of CrN fcc phase on TiN (111) [16,34]. The narrow width of (111) peaks indicates a high degree of crystallinity [16].…”
Section: Chemical Composition and Structure Of Crn/tin Superlattice Cmentioning
confidence: 94%
“…structure with a strong (111)-texture, which represents the well-epitaxial growth of CrN fcc phase on TiN (111) [16,34]. The narrow width of (111) peaks indicates a high degree of crystallinity [16]. There are no distinct Cr 2 N (JCPDS 35-0803) and Ti 2 N (JCPDS 17-0386) phases can be observed in HAXRD patterns.…”
Section: Chemical Composition and Structure Of Crn/tin Superlattice Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Inclination of the TEM sample around the horizontal axis in plane with the layers confirmed that the multilayered structure was not destroyed by the plastic deformation and that there are not cracks in the multilayer coating that is contrary to other studies. 9 Calculated deformation (Table I) A detailed analysis of the multilayer deformation in the center of the indentation can be seen in Fig. 10.…”
Section: E Tem Analysis Of the Deformed Areamentioning
confidence: 99%
“…Figure 1 shows the representative structures of multilayered coatings (a) TiN/CrN and (b) TiAlN/VN. Indeed, the interest in nitride coatings is twofold: transition metal nitrides, which are well classified as refractory compounds, exhibit unusual physical and mechanical properties such as extreme hardness, high thermal-and chemical-stability, good corrosion resistance, and low, stable friction under even dry contact conditions [5][6][7][8][9]. These intriguing properties render them applicable for many uses, for instance, in relation to: engineering tools, magnetic and electric components, superconducting devices, etc., whilst periodic coating of these nitrides in the nano-scale dimension [10,11] onto such tools components and devices can enhance most, if not all, of their functions to a level that none of their individual constituents can ever match [12].…”
Section: Introductionmentioning
confidence: 99%